ANALISIS BIBLIOMETRIK PERKEMBANGAN PENELITIAN BIDANG ILMU INSTRUMENTASI - Tupan, Tupan; Rahayu, Rochani; Rachmawati, Rulina; Rahayu, Endang (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
A study of trend analysis of the field of instrumentation research during the period 2006-2016 was conducted. The study aims to determine: (1) the development of the number of international publications in the field of instrumentation on the Scopus database from 2006-2016; (2) core journals in international publications in the field of instrumentation; (3) productivity of instrumentation researcher; (4) number of documents based on agency collaboration in international publications in the field of instrumentation; (5) the development of international publications of field research instrumentation by subject; (6) maps of international publications development of research in the field of instrumentation by keyword (co-word) and based on the author (co-author). Data collection by searching through scopus with keyword instrumentation, instrumens, measurements, medical instrumentation, virtual instrumentation and instrumentation system with category article title, abstract, keywords in the period 2006-2016. Data in the form of number of publications per year, journals containing articles of instrumentation, author, author and subject are analyzed using Microsoft Excel 2010. As for the development trend of international publications in the field of instrumentation is analyzed using VosViewer software. The results showed that the development of the field of instrumentation sciences during the period 2006-2016 which was scanned in the highest scopus occurred in 2014 which reached 310 documents (14,90%). The international publication of the field of instrumentation is mostly published in the journal Spine. Universidade de São Paulo - USP is the most widely published institution in the field of instrumentation science and the United States is the largest contributor. Yazici, M., Zhang, H.Q., and Aubin, C.E. is a prolific writer in the field of instrumentation with the most subjects in medicine and engineering. The map of instrumentation development based on the coword grouped into 5 clusters and the co-authors clustered into 7 clusters.